Sociodemographic determinants of prepregnancy body mass index and gestational weight gain: The Mutaba'ah study. (11th November 2021) - Cheng, Tuck Seng; Ali, Nasloon; Elbarazi, Iffat; Al‐Rifai, Rami H.; Al‐Maskari, Fatma; Loney, Tom; Ahmed, Luai A.
Abstract: Objective: This study examined the associations of sociodemographic and lifestyle factors with prepregnancy body mass index (BMI) and gestational weight gain (GWG). Methods: In the Mutaba'ah Study in the United Arab Emirates, repeated measurements throughout pregnancy from medical records were used to determine prepregnancy BMI and GWG. Associations of sociodemographic and lifestyle factors with prepregnancy BMI and GWG (separately by normal weight, overweight, and obesity status) were tested using multivariable regression models, adjusted for maternal age at delivery. Results: Among 3536 pregnant participants, more than half had prepregnancy overweight (33.2%) or obesity (26.9%), and nearly three‐quarters had inadequate (34.2%) or excessive (38.2%) GWG. Higher parity ( β for 1–2 to ≥5 children = 0.94 to 1.73 kg/m 2 ), lower maternal education ( β for tertiary = −1.42), infertility treatment ( β  = 0.69), and maternal prepregnancy active smoking ( β  = 1.95) were independently associated with higher prepregnancy BMI. Higher parity was associated with a lower risk for excessive GWG among women with prepregnancy normal weight (odds ratios (ORs) for 1–2 to ≥5 children = 0.61 to 0.39). Higher maternal education was negatively associated with inadequate GWG among women with normal weight and overweight (ORs for tertiary education = 0.75 and 0.69, respectively). Conclusions: Sociodemographic factors, especially parity and maternal education, were differentially associated with prepregnancy BMI and GWG adequacy across weight status.